Kebijakan Pertanahan Bagi WNI Keturunan Tionghoa Di Yogyakarta: Diskrimasi Atau Diskriminasi Positif - Lestarini, Ratih (UI Scholars Hub, 2018)
This paper intends to examine the enforcement of land policy related land rights for Indonesian citizens of Chinese descent in the Territory Special Region of Yogyakarta. In this context, they can only be granted land rights in the form of HGB, not allowed to obtain property rights to land in Yogyakarta. This restriction is considered as a different treatment of citizens of Chinese descent. This issue becomes important to be discussed considering the Law No. 5 of 1960 on Agrarian Principles ensuring the arrangement of land tenure is directed to be utilized for all Indonesian citizens without exception in a fair manner. The discussion of the issue will be further elaboratedusing the perspective of the sociology of law in order to explain how the people of Yogyakarta responded to such policy.